Dynamic Transformations in Fruit Color, Bioactive Compounds, and Textural Characteristics of Purple-Fleshed Dragon Fruit (Hylocereus costaricensis) Across Fruit Developmental Stages Under Humid Tropical Climate - Sajitha Shameena; Prabhakaran Radhamma Geetha Lekshmi; Pratheesh Pradeep Gopinath; Praveen Gidagiri; Selvaraju Kanagarajan (Horticulturae)
Purple-fleshed dragon fruit is gaining popularity worldwide due to its distinctive characteristics and health benefits. This climbing cactus, introduced to humid tropical climates, presents challenges in assessing fruit quality. The dynamic transformations in fruit color, bioactive compounds, and textural attributes across 11 developmental stages from 10 to 32 days after flowering under humid tropical conditions were studied. Color analysis revealed significant intensification of red-violet hues, with L* values decreasing by 14.74% and a* values increasing from −8.14 to 32.96. The color transformation is initiated in the pulp at 25 days and the peel at 27 days after flowering. Betalain synthesis commenced after 20 days with rapid accumulation between 25 and 32 days, correlating with color development. Antioxidant activity increased from 79.38% at 10 days to 86.76% at 20 days, followed by a steady decline. Phenolic content peaked at 121.40 mg gallic acid equivalent per 100 g at 25 days before declining, while the flavonoid content decreased with the advancement of fruit development. Concurrent reduction in peel thickness and fruit firmness was also observed. These findings show that purple-fleshed dragon fruit can adapt well to humid tropical conditions, with a 32-day developmental cycle, offering vital insights into quality and maturation phases.